2010
DOI: 10.1007/s11356-010-0342-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acetaminophen in Brassica juncea L. Czern.: investigation of uptake, translocation, detoxification, and the induced defense pathways

Abstract: The major metabolic pathways in mammals are conjugation with activated sulfate and glucuronic acid, while a small amount of acetaminophen forms a chemically reactive and highly toxic, hydroxylated metabolite. We identified a glutathionyl and a glycoside conjugate, which refer to the similarities to mammalian detoxification. Increased GST activities in leaf tissues were observed correlated with the appearance of the acetaminophen-glutathione conjugate which shows the involvement of this enzyme group in the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 29 publications
7
61
0
Order By: Relevance
“…Huber and coworkers exposed barley and a hairy root cell culture of horseradish to diclofenac and acetaminophen, and identified two metabolites of diclofenac in plants (Huber et al, 2012): 4-OHdiclofenac (phase I metabolite) and 4-OH-diclofenac glucopyranoside (phase II metabolite); and three phase II metabolites of acetaminophen (Huber et al, 2009): acetaminophen glucoside, acetaminophen glutathione, and the corresponding cysteine conjugate. In Indian mustard, the same authors observed that concentrations of acetaminophen in plant tissues significantly decreased after a 24-h exposure, which was concurrent to an increase in the glutathione S-transferase (GST) activity in leaves and the appearance of the acetaminophen-glutathione conjugate (Bartha et al, 2010).…”
Section: Metabolism Of Ppcps In Plantsmentioning
confidence: 92%
See 3 more Smart Citations
“…Huber and coworkers exposed barley and a hairy root cell culture of horseradish to diclofenac and acetaminophen, and identified two metabolites of diclofenac in plants (Huber et al, 2012): 4-OHdiclofenac (phase I metabolite) and 4-OH-diclofenac glucopyranoside (phase II metabolite); and three phase II metabolites of acetaminophen (Huber et al, 2009): acetaminophen glucoside, acetaminophen glutathione, and the corresponding cysteine conjugate. In Indian mustard, the same authors observed that concentrations of acetaminophen in plant tissues significantly decreased after a 24-h exposure, which was concurrent to an increase in the glutathione S-transferase (GST) activity in leaves and the appearance of the acetaminophen-glutathione conjugate (Bartha et al, 2010).…”
Section: Metabolism Of Ppcps In Plantsmentioning
confidence: 92%
“…A number of studies have been performed under hydroponic conditions to evaluate the bioaccumulation potentials of PPCPs in plants and explore uptake mechanisms under simplified conditions (Bartha et al, 2010;Calderón-Preciado et al, 2012;Dodgen et al, 2013Dodgen et al, , 2015Herklotz et al, 2010;Redshaw et al, 2008;Shenker et al, 2011;Tanoue et al, 2012;Wu et al, 2013). The extent of PPCP uptake by plants is usually evaluated using bioconcentration factor (BCF), which is the ratio of the analyte concentration detected in the plant tissue to the spiked concentration in the growth medium.…”
Section: Ppcps In Plants Grown Under Hydroponic Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The collision energy and collision cell exit potential for the m/z 452/306 transition were set to 25 and 10 V, respectively. The transition ion pair for quantitation of the internal standard (AP-GSH) was 457/328 (Bartha et al, 2010) with the collision energy and collision cell exit potential set as 30 and 10 V, respectively. The retention time for NA-GSH was ϳ10.18 min and that for AP-GSH was ϳ8.90 min.…”
Section: Methodsmentioning
confidence: 99%